2022
DOI: 10.1021/acs.jmedchem.2c01133
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Evaluation of Second-Generation Soluble Adenylyl Cyclase (sAC, ADCY10) Inhibitors with Slow Dissociation Rates

Abstract: Soluble adenylyl cyclase (sAC: ADCY10) is an enzyme involved in intracellular signaling. Inhibition of sAC has potential therapeutic utility in a number of areas. For example, sAC is integral to successful male fertility: sAC activation is required for sperm motility and ability to undergo the acrosome reaction, two processes central to oocyte fertilization. Pharmacologic evaluation of existing sAC inhibitors for utility as on-demand, nonhormonal male contraceptives suggested that both high intrinsic potency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…1d ). TDI-11861 is highly specific for sAC; it had no activity against tmACs from each subfamily 37 .
Fig.
…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…1d ). TDI-11861 is highly specific for sAC; it had no activity against tmACs from each subfamily 37 .
Fig.
…”
Section: Resultsmentioning
confidence: 97%
“…However, in addition to exploiting the bicarbonate binding site engaged by LRE1 and TDI-10229, TDI-11861 also occupies a channel leading to the active site (Fig. 1b ) 35 , 37 . Thus, TDI-11861 binds sAC protein tighter and inhibits the in vitro adenylyl cyclase activity of purified sAC protein with an improved IC 50 of 3 nM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted November 29, 2022. ; https://doi.org/10.1101/2022.11.28.518282 doi: bioRxiv preprint Miller et al found a novel compound TDI-11861 which shows both improved sAC (ADCY10) binding affinity and residence time than its precursor (3181 s versus to 25 s). 61 Combining induced fit docking and MM/GBSA calculation cubic by cubic, Bai et al, construct a sophisticated energy landscape of ligand dissociation and found a potential lead compound which shows better binding kinetic and thermodynamic properties with either TcAChE or mAChE. 62 Here, we combine ML, accelerated MD and similarity search to find potential molecules with longer retention time than their precursors.…”
mentioning
confidence: 99%